ANALYSIS OF THE STICKY COSTS BY KINDS OF COSTS ON B3 LISTED INDUSTRIES - Figueira Marquezan, Luiz Henrique (2024)
The research objective was to analyse the costs behaviour by kinds of the costs, in relation to fluctuations in the volume of activities, in B3 listed industries. For this purpose, a descriptive and quantitative approach was used, with secondary data from the financial statements from 2010 to 2018 of the sample companies. The data were submitted to regression analysis of panel data. The results found point to asymmetry in the costs behaviour of the analysed industries, with greater emphasis on reducing the cost when there is a reduction in sales than when there is an increase. For labour costs, depreciation, goods and raw material, the findings point to asymmetry. Labour costs and depreciation reveal asymmetry, oscillating only when there is a reduction in sales, and without statistically significant relationship with increases in sales. For goods and raw material, the results reveal that there is asymmetry and the greatest emphasis for increasing the cost when there is an increase in sales. These results contribute to teachers, students and researchers in the teaching and learning process and to new researches; for accountants and managers contributes, because the results seek a better understanding about the behaviour of their companies' costs, possible by the analysis by nature of the costs.